Swot Analysis of Pharmacy Department Development Strategy in X Hospital in East Kalimantan Province - Amalia Yuliasari; Annisari Pinasthika; Firda Diah Utami; Hany Setyo Utami; Mira Veranita (Yayasan Adra Karima Hubbi, 2023)
The hospital is an institution that provides health services and is an institution that cannot be separated from the influence of the internal and external environment. The growth and development of the hospital can be influenced by the organizational environment where the hospital is located. Therefore, a hospital management system is needed that considers strategic aspects so that the hospital can adapt and control the factors that influence and continue to change, both internal and external factors. The purpose of this study was to determine the position of the X Hospital Pharmacy Installation in the province of East Kalimantan towards the internal and external environment through a SWOT analysis and identify alternative strategies for development with the SWOT method. Research using a qualitative descriptive design using a questionnaire. Data on the strengths, weaknesses, opportunities, and threats of the Pharmacy Installation were obtained by observation and in-depth interviews. From the SWOT analysis, a SWOT matrix is obtained based on the External Factor Analysis Summary (EFAS) and the Internal Factor Analysis Summary (IFAS). The results of the study show that the Pharmacy Installation of X Hospital is in quadrant two with a diversification strategy to implement its development strategy. The RS X's internal strength factor is 1.11 times greater than its weakness and the results are opportunities that are smaller than the threats.